A Price to Pay for Adult Neurogenesis - Schinder, Alejandro Fabian (2014)
We tend to believe that plasticity is what makes brain circuits adaptable to continuous changes in environmental demands and that greater brain plasticity should result in a better ability to cope with the surrounding world. To adapt to everyday life, animals explore, learn, and remember, and these tasks make use of various cortical structures, including the hippocampus. The dentate gyrus, part of the hippocampus, is a remarkable structure in that it is one of two areas of the adult mammalian brain, including the human brain, that continue to generate new neurons throughout postnatal life (1). It is well established that adult-born neurons integrate into preexisting neuronal networks and participate in information processing (2). Much evidence accumulated over the past decade supports the hypothesis that adult neurogenesis itself is a type of circuit plasticity required for hippocampus-dependent learning and memory recall. The work by Akers et al. on page 598 of this issue (3) now shows that adult hippocampal neurogenesis may also promote forgetting.